Transactional Analysis for Developing Student Social Relationships - Fikriyanda Fikriyanda; Netrawati Netrawati; Yeni Karneli; Neviyarni Neviyarni (Universitas Negeri Padang, 2021)
Eachlife span has a developmental task to go through. One of the most challenging developmental tasks associated with adolescence is the developing social relationships with other people. This ability is essential for everyone because it can affect various aspects of life. In educational institutions, school counselors can use transactional analysis theory to develop students' social relationship skills because this theory is based on social relationships and transaction. This article will discuss the role of transactional analysis theories and approaches to develop students' social relationships using the method of literature study. It can be used as an alternative used by school counselors to optimize student development, especially in social relationship and interpersonal communication skills.